Students’ Attitudes towards Selling Products via Social Media - Bensoh et al., Thananchanok (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this study were 1) to study students’ attitudes towards selling products through social media and 2) to compare students’ attitudes which classified to the personal factors. A sample was 600 first-to-fourth year students from Songkhla Rajabhat University, Thaksin University and Rajamangala University of Technology Srivijaya. The questionnaire as a tool was used to collect data. Statistics used in data analysis were frequency, percentage, mean, standard deviation, independent sample t-test, One Way ANOVA and pairwise comparison by Fisher’s Least Significant Difference (LSD) if the variances of the groups were equal and Dunnett’s T3 if the variances of the groups were not equal. The results found that the affective, cognitive and behavioral components of students’ attitude towards selling products through social media were at a high level. Moreover, the overall attitudes of students towards selling products via social media were at a high level. The results of hypotheses testing revealed that the students with different gender, age, experience of goods purchasing via social media, university, faculty and academic year had statistical difference in the attitudes towards selling products through social media, while the students with different the monthly income had no statistical difference in the attitudes towards selling products through social media. Article history : Received 11 May 2019 Revised 6 June 2019 Accepted 9 June 2019 SIMILARITY INDEX = 0.00 %